Comparison of the progressive collapse resistances of different single-layer latticed domes. (November 2019) - Tian, Li-min; Nie, Xiao-ning; Zhong, Wei-hui; Wei, Jian-peng
Abstract: This study conducted progressive collapse tests of Keiwitt-6 (K6) and three-way diagonal grid (TD) single-layer latticed domes. Progressive collapse tests of single-layer latticed domes were performed to examine the dynamic responses, collapse mechanisms, and collapse modes of different structural types after the failure of multiple structural members. The results indicated the following: 1) Under the same test conditions, two types of structures exhibited the same collapse mode: local collapse occurred first at the destructive part of the structures; then, with increases in the number of failed members, the collapse range continuously expanded, and the structures ultimately exhibited complete collapse. Some of the members at the supports exhibited cracks or necking. 2) The K6 and TD single-layer latticed domes relied on the compression and beam mechanisms, respectively, to resist progressive collapse. 3) The K6 single-layer latticed dome exhibited better resistance to progressive collapse as compared to that of the TD single-layer latticed dome. 4) The progressive collapse resistances of K6 and TD single-layer latticed domes were significantly improved by increasing the bending stiffness of radial members. Highlights: Progressive collapse tests of K6 and TD single-layer latticed domes were conducted. An electronic device was designed to remove a single member instantaneously. Mechanisms of two types of domes were proposed to resist progressive collapse. Collapse resistance was improved by increasing the bending stiffness of radial members.